Hubungan Body Condition Score dengan Service Per Conception pada Induk Sapi Bali di Desa Kilang Kecamatan Montong Gading Kabupaten Lombok Timur - Sabaruddin; Kholik; Dina Oktaviana; Maratun Jannah (Jurnal Sains Peternakan, 2022)
One indicator of success in reproductive efficiency in artificially inseminated (IB) cattle is the Service per Conception (S/C) value, which is widely associated with the body condition score of the cow known as the Body Condition Score (BCS). The purpose of this study was to determine the relationship between value of BCS and S/C of Bali cattle in artificial insemination of Bali cattle. The type of research is an observational longitudinal study, which was conducted from January to April 2021 in the Kilang village Montong Gading district. The number of samples used in this study was 20 Bali cattle with a purposive sampling method on Bali cattle with two lactations. Assessment of Body Condition Score (BCS) is done visually or by palpation on body fat deposits under the skin around the base of the tail, vertebrae and coccyx, while the S/C score is assessed by comparing the number of artificially inseminated (IB) to the occurrence of pregnancy. The relationship between BSC and S/C was carried out using the Pearson Chi-square test. The results showed that the 20 Bali cattle that were sampled had an average Body Condition Score of 2.4 ± 0.680, while the Service per Conception value had an average of 1.55 ± 0.686. The results of the Pearson Chi-square test analysis regarding the relationship between Body Condition Score and Service per Conception in Bali cattle did not have a non-significant relationship because p-value > 0.05 (p-value = 0.08) with = 0.05.